AMBIQUITY OF COLONIAL-AFGHAN AGENCY IN KHALED HOSSEINI’S THE KITE RUNNER AND THE MOUNTAINS ECHOED A POSTCOLONIAL READING - Sharma, Tushar; Rana, Sujata (ShodhKosh: Journal of Visual and Performing Arts, 2026)
This article explores Khaled Hossieni’s The Kite Runner and the Mountains Echoed in the context of responsibility to respond on behalf of Afghanistan post 9/11 or reinforces colonial hegemonies. It suggests that while Hosseini’s both novels capture that socio-cultural problems like gender, ethnicity and religious extremism in the graveyard of empires. Although the novels oscillate between western exceptionalism and Afghan agency, I argue that the creates an ambiguous identity.